DIGITAL STRESS IN EVERYDAY LIFE - Wimmer, Jeffrey; Waldenburger, Lisa (AoIR Selected Papers of Internet Research, 2020)
In our paper we want to explore inductively the perceived characteristics and forms of digital stress in people’s everyday life. How do they describe digital stress, is it different from other forms of stress and how does digital stress express itself? The focus is not genuinely on the topic of digital stress, but on the attempt to make this phenomenon empirically tangible and to link it to concepts of digital wellbeing. If everyday discourses are primarily concerned with new possibilities or negative implications associated with the use of digital technologies and media, we would like to turn to a more holistic perspective which builds on subjective perceptions as well as practices. This ensures not only that the ambivalent potential of digital media is taken into account, but also that the media repertoire of the users is considered in its full complexity